Environmental Policy Can Happen: Shuttle Diplomacy and the Reality of Reg Neg Lite. (28th December 2013) - Rinfret, Sara; Cook, Jeffrey
ABSTRACT In an era of congressional gridlock, innovation and pathways for the future of environmental policymaking are needed. The US Environmental Protection Agency (EPA) has long been an innovator in environmental decisionmaking, reconciling stakeholder differences. Yet, with the decline of negotiated rulemaking ('reg neg'), the purpose of our examination is to offer insights into how a contemporary US EPA creates rules. This exploratory study examines original interview data from actors involved during the creation of EPA rules to suggest that a present‐day EPA uses a new approach, shuttle diplomacy, to develop rules. The findings from our research suggest that this new rule development method can help agencies that might operate in an adversarial environment to reconcile stakeholder differences while writing the language of a proposed rule before publishing a Notice of Proposed Rulemaking. We argue that this new rule development model is important for understanding the next generation of environmental rulemaking, not only in the US, but internationally as well. Copyright © 2013 John Wiley & Sons, Ltd and ERP Environment.